Collaboration across cultures: planning and delivering professional development for inclusive education in India. Issue 3 (29th September 2015) - Rose, Richard; Doveston, Mary
<x xml:space="preserve">Abstract</x> In recent years a number of western universities have established professional development courses in international contexts. These have often involved tutors travelling to countries with which they may have previously had little contact, in order to deliver courses that have been long established in their own universities. This article discusses some of the challenges of working in international contexts, and suggests that respectful professional development must be founded upon equitable partnerships that involve local colleagues. It is suggested that time needs to be invested in understanding national and local initiatives in order to place these within the context of international developments, and that knowledge of local schools and resources is essential to the effective development and delivery of courses. The article is based upon the experiences of tutors from the UK who have been working alongside colleagues from India in the delivery of professional development over many years, and more recently in the management of an MA programme in Special and Inclusive Education in Bangalore.